2014
DOI: 10.1007/s00125-014-3483-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of diluted (U20) insulin aspart compared with standard (U100) in children aged 3–6 years with type 1 diabetes during closed-loop insulin delivery: a randomised clinical trial

Abstract: Aims/hypothesisThe aim of this study was to compare the pharmacokinetics of two different concentrations of insulin aspart (B28Asp human insulin) in children aged 3–6 years with type 1 diabetes.MethodsYoung children with type 1 diabetes underwent an open-label, randomised, two-period crossover study in a clinical research facility, 2–6 weeks apart. In random order, diluted (1:5 dilution with saline [154 mmol/l NaCl]; 20 U/ml) or standard strength (100 U/ml) insulin aspart was administered via an insulin pump a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…Elleri et al (34) reported that use of diluted insulin during overnight closed-loop control in 3-to 6-year-olds reduced rates of hypoglycemia and tended toward reduced glycemic variability as compared with standard insulin strength. Additionally, analysis of the data from that study demonstrated reduced interindividual variability in time to peak insulin action with diluted insulin (35). The reduced interindividual variability could be attributed to a reduction of mechanical delivery errors and more consistent absorption due to the larger volume of the subcutaneous deposit (35).…”
Section: New Features To Promote Hcl Use In Pediatricsmentioning
confidence: 77%
See 1 more Smart Citation
“…Elleri et al (34) reported that use of diluted insulin during overnight closed-loop control in 3-to 6-year-olds reduced rates of hypoglycemia and tended toward reduced glycemic variability as compared with standard insulin strength. Additionally, analysis of the data from that study demonstrated reduced interindividual variability in time to peak insulin action with diluted insulin (35). The reduced interindividual variability could be attributed to a reduction of mechanical delivery errors and more consistent absorption due to the larger volume of the subcutaneous deposit (35).…”
Section: New Features To Promote Hcl Use In Pediatricsmentioning
confidence: 77%
“…Additionally, analysis of the data from that study demonstrated reduced interindividual variability in time to peak insulin action with diluted insulin (35). The reduced interindividual variability could be attributed to a reduction of mechanical delivery errors and more consistent absorption due to the larger volume of the subcutaneous deposit (35). Hvorka and colleagues are conducting an open-label, randomized crossover assessment of diluted insulin as compared with commercially available insulin preparations in children aged 1-7 years (NCT03101865).…”
Section: New Features To Promote Hcl Use In Pediatricsmentioning
confidence: 99%
“…Recently, an ISPAD Clinical Practice Consensus Guideline has been released entitled “Managing Diabetes in Preschool Children,” which states pump therapy is the recommended mode of insulin delivery for those under the age of 7 years . In order to overcome the mechanical barrier dictated by the lowest basal and bolus delivery doses feasible with pump therapy, application of diluted insulin to the youngest population has offered the opportunity to more finely tune insulin delivery . While concern is sometimes expressed over how paid care providers will adopt this technology, a study by Weinzimer et al highlighted that children whose parents work outside of home tended to see the largest improvement in glycemic control with transition to pump therapy …”
Section: Insulin Pumpsmentioning
confidence: 99%
“…Of note is that differences in duration of action have been noted at the more concentrated end of the spectrum in U300 glargine 20 and U500R 21 insulin. It is encouraging to note that a recent study by Ruan et al 22 compared U10 or U100 insulin administered by pump with overnight closedloop delivery and showed no difference in pharmacokinetics. However, further study is warranted to understand the pharmacodynamics of diluted insulin in young children and whether varying dilutions behave significantly differently.…”
Section: Diabetes Technology and Therapeuticsmentioning
confidence: 96%